IMPLEMENTASI MANAJEMEN RISIKO DALAM MENGATASI PERMASALAHAN PEMBIAYAAN MURABAHAH DI BMT AL-HIJRAH BUKITTINGGI - Ayu Ayu; Ariyun Anisah (Adisam Publisher, 2025)
The problem studied in this study is about the implementation of risk management in dealing with problematic murabahah financing at BMT Al-Hijrah Bukittinggi. The purpose of this study is to analyze the implementation of risk management in overcoming problematic murabahah financing at the institution. This type of research is classified as Descriptive Qualitative Research. Descriptive Qualitative Research is recognized as one type of research within the qualitative research category, where events and phenomena from individual lives are studied, and one or a group of people are asked to share their life experiences. In this approach, data is collected through methods of observation, interviews, and documentation. Data analysis is conducted in three main phases: data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of risk management in Murabahah financing at BMT Al Hijrah Bukittinggi has been carried out effectively. This is evidenced by the determination of requirements when financing is submitted and the implementation of a structured risk management process. The first step taken involves risk identification, which is conducted by applying the 5C principle (Character, Capacity, Capital, Collateral, and Economic Condition) along with 3R (Rescheduling, Reconditioning, and Restructuring), adjusted to the conditions and characteristics, as well as Sharia rules that prohibit business activities contrary to the teachings of Allah and government regulations. The identification process is conducted through the examination of financing needs, direct observation in the field, and reference to applicable policies. Furthermore, risk measurement is performed by grouping the quality of financing, followed by risk monitoring through routine inspections. Risk control is implemented through various steps, such as intensive monitoring, the setting of financing limits, the avoidance of risky financing, debt collection, the sending of reminder letters, and the provision of advice to customers. Although this risk management is implemented well, the risk cannot be completely eliminated. Therefore, the importance of risk prevention efforts is strongly emphasized by BMT Al Hijrah through understanding, assessing, measuring, and managing risks according to their nature.